Development of Trait Emotional Intelligence in Response to Childbirth: A Longitudinal Couple Perspective - Galdiolo, Sarah; Gaugue, Justine; Mikolajczak, Moïra; Van Cappellen, Patty (Frontiers in Psychiatry, 2020)
The aim of the current paper was to investigate the influence of childbirth on parents’ trait emotional intelligence (EI). A three-wave longitudinal research program (during the second trimester of pregnancy, at 6 months postpartum, and at 1 year postpartum) using the Actor-Partner Interdependence Model with a hierarchical linear modeling was conducted on 204 parental couples with parental group (i.e., primiparous and multiparous parents) as a time-invariant predictor and the partner’s EI development as a time-varying covariate. Results showed that parents’ EI was stable, except for Self-Control that increases after childbirth. Moreover, there was a significant negative association between the actor’s and the partner’s development around childbirth. Childbirth pushes parents to function in dyad rather than individually. Compensatory effects may be observed between both parents in terms of emotional management of parenting: When one partner cannot cope emotionally with parenting, the other partner would compensate and better manage the emotional aspects of parenting. The discussion underlined the importance of the dyadic perspective in understanding the childbirth experience, specifically the parents’ receptivity to variation in their partners’ emotional levels.